Transistor using two-dimensional electron gas in thin film oxide heterostructure via atomic layer deposition - Kim, Hye Ju; Kim, Seong Hwan; Lee, Sang Woon (Proceedings of the World Congress on New Technologies, 2019)
Two-dimensional electron gas (2DEG) at an epitaxial interface of LaAlO3/SrTiO3 (LAO/STO) heterostructures has received considerable attentions because of their unique physical properties.[1] Electrons at the interface of LAO/STO heterostructure move freely along in-plane direction while they are confined in 1~2 nm range of out-of-plane direction. The electron density of 2DEG at LAO/STO heterostructure is 1013~1014/cm2 which is 100 times higher than those of the conventional semiconductor heterojunction such as AlGaAs/GaAs. The high density of electrons enables a fabrication of high-performance transistor. Unfortunately, the growth of LAO epitaxial layer on single crystalline STO substrate is necessary for 2DEG generation via polar catastrophe mechanism which impeded a practical use of the oxide heterostructure. Here, we demonstrated a creation of 2DEG at the non-epitaxial interface of Al2O3/TiO2 (<15 nm) thin film heterostructure via atomic layer deposition (ALD), without using single crystalline STO substrate for the first time.[2] By implementing ALD, the mature thin film process can facilitate mass production as well as three-dimensional integration of the devices. The electrical properties of thin film Al2O3/TiO2 heterostructure are similar with those of the epitaxial LAO/STO heterostructures. It was observed that high density electrons up to (1013~1014/cm2) were confined within ~2.2 nm of the interface of the Al2O3/TiO2 heterostructure. Interestingly, the electron density can be adjusted from ~ 1011/cm2 to ~ 1014/cm2 by the control of ALD process temperature because the free electrons are created by the formation of oxygen vacancies at the interface of Al2O3/TiO2 heterostructure of which kinetics is governed by the ALD process temperature. Those oxides (Al2O3 and TiO2) are transparent insulators with wide bandgaps (>3.2 eV) which implies a possible application of transparent devices. With the Al2O3/TiO2 thin film heterostructure, a transparent thin film transistor (TFT) was fabricated which outperforms conventional TFTs. A high on-current (Ion, > 12 μA/μm), high on/off current ratio (Ion/Ioff > ~108), low off-current (Ioff, ~10- 8 μA/μm), and low sub-threshold swing (SS, ~100 mV/dec.) are achieved. Besides the TFT application, a high-performance transparent hydrogen (H2) gas sensor was developed using the 2DEG at Al2O3/TiO2 thin film heterostructure which shows a sensitive detection of H2 gas even at room temperature.[3] It exhibited a reliable detection with a fast response speed (<30 s) for H2 concentration as low as 5 ppm which outperforms conventional H2 gas sensors operating at room temperature, indicating that heating modules are not required for the rapid detection of H2. The gas sensor can detect H2 gas across a wide range of concentrations, from 5 ppm to 1%, implying that it is a promising candidate for a general H2 sensor. The H2 gas sensor using 2DEG was fabricated on a polyimide substrate which enabled a fabrication of flexible gar sensor. The H2 sensing performance was maintained even after bending cycles of 500 with a bending radius of 10 mm. After all, the creation and control of 2DEG at thin film oxide heterostructure using ALD, and their applications will be addressed in the presentation.